ARABIC LEARNING IN THE DIGITAL ERA: APPROACH IN ONLINE SYSTEM - Zainul Arifin; Suci Ramadhanti Febriani; Hendri Yahya Saputra; Anasruddin Anasruddin (IAIN Batusangkar, Indonesia, 2021)
One alternative to learning Arabic in the digital era is through online learning using digital technology. The process of learning Arabic in Indonesia has developed rapidly in recent times. The transition from face-to-face to online classes requires adjustments in the learning approach. This research used literature review method. Sources of data were books, articles, and other relevant sources. Data were analyzed through data collection procedures, data grouping, data display, and drawing conclusion. The validity of the data was tested through source and technical triangulation. The result of the study indicated that there are three appropriate approaches for learning Arabic online in this digital era, namely the contextual approach, constructivism approach, and behaviorism approach. The choice of approach should meet the students’ needs and learning conditions. Each approach could be implemented through a variety of methods and techniques. The integration of these three approaches in learning Arabic online provides broad opportunities for students to study independently and develop language skills aspects through various available digital media platforms.